Dasturlash tillari resurslaridan foydalanib talabalarning malaka amaliyot jarayonlarini pedagogik loyihalashtirish - Avezov, M.A (SCIENCE and SOCIETY, 2025)
The article discusses the issues of pedagogical design of students' qualification practice processes with the help of programming languages and information-communication technologies.
Keywords: programming languages; ICT; modern education system; software; open educational resources; education types